Efficiency of Snatch Technique in High Level Weightlifters - Anatoly Shalmanov; Vitaly Skotnikov; Elena Lukunina; Janis Lanka (Lithuanian Sports University, 2018)
Background. Rich theoretical and experimental evidence on the biomechanics of weightlifting exercises has currently been collected (Bauman, Gross, & Quade, 1988; Garhammer, 1991; Gourgoulis, Aggelousis, & Mavromatis, 2000; Isaka, Okada, & Funato, 1996; Шалманов, Скотников, & Панин, 2012). Most of the studies were mainly carried out in laboratory settings, with long-term treatment of the obtained data. In recent years, scientists' interest has shifted to the study and evaluation of the technical mastery of athletes in the setting of the highest level competition, in  the  extreme  conditions  of  sport  fight.  This  was  facilitated  by  the  development  of  specialized  hardware  and program sets (Шалманов & Скотников, 2013; Шалманов, Скотников & Ланка, 2013), opening the possibility for biomechanical control of athletes technical and speed-strength fitness both during the technical training process and competition. One of the ways of evaluating the effectiveness of techniques is based on the idea of using motor capacity by an athlete, which is called efficiency of realization. Methods. To register the trajectory of the bar and calculate kinematic and dynamic parameters of its movement a specialized hardware-program complex (APC) has been developed. In the APC, a photo-video camera "Canon" is included; a marker is fixed on the end of the bar as well as a computer with software. Recording was carried out during major competitions (Cup of Russia, the Russian Championship, and the XХVII World Summer Universiade) in 2012-2014. The total number of athletes surveyed was 331 people (184 men, 147 women). The paper presents the results obtained in the snatch in men. Results. The regularities in the change of kinematic and dynamic bar movement parameter with an increase in weight category and sport result were determined. The main indicator determining sports result in a classic snatch was the absolute maximum power developed by the athlete during acceleration of the bar in the final phase of its lifting: r = .75, p < .001. The indicator of absolute power is the most informative to assess the level of athlete speed- strength fitness, realized due to the efficiency of sports technique and prediction of sports result. Conclusions. The regression equation between the result in the snatch and the maximum absolute power in the final acceleration of the bar give a possibility to evaluate the technique of the effectiveness of each athlete: if it is better or worse than the average one and to what extent. This analysis gave one more possibility - to compare the set up performance with the performance that the athlete, taking into account their level of physical conditioning (maximal power), would achieve if they improve their technique. Keywords:  biomechanical control, technical and physical fitness, technique realization ef fectiveness